Shientific heritage of the Academy of Sciences of the UAS GA Bogdano in the context of environmental monitoring of livestock in zones of radioactive contamination - Kashpersky, V. E. (History of science and technology, 2018)
It is highlighted the contribution of the doctor of agricultural sciences, academician of the UAAS G.A. Bogdanov in the development of scientific bases for the management of livestock in radioactively contaminated lands. The main components of his scientific heritage are generalized: agronomic and technological measures to reduce the input of radionuclides in fodder crops, the organization of fodder production, balancing of rations on sugar, protein and trace elements, and the inclusion of sorbents in animal rations. The analysis of his scientific works on the given problem has been carried out.